Application of Shark Teeth–Derived Bioapatites as a Bone Substitute in Veterinary Orthopedics. Preliminary Clinical Trial in Dogs and Cats - García-González, Mario; Muñoz Guzón, Fernando María; González-Cantalapiedra, Antonio; González-Fernández, Pío Manuel; Otero Pérez, Rafael; Serra Rodríguez, Julia Asunción (Frontiers in Veterinary Science, 2020)
Background. The autograft is still considered the gold standard for the treatment of bone defects. However, given the significant morbidity of the donor site with which it has been associated, alternative substitutes for bone grafts have been developed. In the present study, a bone substitute composed of CaP biphasic bioceramics obtained from shark teeth was used (BIOFAST-VET). Objective. The objective of this study is to evaluate the efficacy of a marine bioapatite in the veterinary clinical field using it as a bone grafting scaffold in dogs and cats. Methods. The biomaterial was randomly distributed in 6 veterinary clinical centers in Spain and was used in 24 cases (20 dogs and 4 cats) including 14 fractures, 9 arthrodesis and 1 bone cyst. Grains between 500 and 2000 micrometers were used. Inclusion and exclusion criteria were established. The time of consolidation and functional recovery were quantitatively and qualitatively assessed. For this, a follow-up was carried out at 2, 4, 8 and 12 weeks, included radiographic images, physical examination and sharing the feedback with the owners. Results. 19 cases completed the study (18 dogs and 1 cat; 11 fractures, 7 arthrodesis and 1 bone cyst). The remaining 5 were excluded because they did not complete the radiographic follow-up (3 cats and 2 dogs, being 3 arthrodesis and 2 fractures. In 18 out of 19 cases, the use of the biomaterial was successful; the remaining one failed due to causes not related to the biomaterial. There were no systemic or local adverse reactions. 18 patients had a good functional recovery. The average consolidation time was 5.94 weeks in dogs with fractures and arthrodesis, not finding statistically significant differences between sex, weight and procedure. Conclusions. This biomaterial is presented as a very suitable candidate for orthopedic surgery in the veterinary field. Preliminary results showed that its use reduces consolidation time in dogs with fractures and arthrodesis. In addition, no adverse or local reactions have been observed derived from its use.